The influence of business capital and cost of space rent (ijarah) on merchants’ income in the traditional market of Lau Dendang Village - Pane, Muhammad Rivaldi; Nasution, Muhammad Lathief Ilhamy; Harahap, Muhammad Ikhsan (Universitas Islam Indonesia, 2024)
IntroductionPrevious research has been carried out to analyze variables that influence traditional traders' income. However, research with the variables working capital and rental costs in the context of Lau Dendang Village has not been carried out.ObjectivesThis research was carried out with the aim of finding out the relationship between business capital and rental costs (Ijarah) on trading income in the traditional market of Lau Dendang Village.MethodThis research was conducted and carried out using quantitative methods and uses data obtained from sampling using research instruments in the form of questionnaires with the population being traders in several markets in Lau Dendang Village.ResultsThe results of the research that has been carried out are that a negative and significant influence is obtained on the variable working capital and rental costs as independent variables on merchants income as dependent variable.ImplicationsMerchants in traditional market should have adequate capital of their own and need support to lower rental costs to increase their income.Originality/NoveltyThis study contributes to enrich studies in the field of Islamic economics related to the income of traders in traditional markets.